PENINGKATAN HASIL BELAJAR CIRI-CIRI BANGUN DATAR MENGGUNAKAN MODEL COOPERATIVE TIPE MAKE A MATCH BERBANTUAN WORDWALL DI KELAS IV SDN 20 BINUANG KAMPUNG DALAM KOTA PADANG - Anyelir, Erica; Suciana, Fadila; Ahmad, Syafri; Wulandari, Fikhen Tri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of student engagement in the learning process, lack of enthusiasm and motivation to learn, and students’ tendency to be easily distracted. These conditions were caused by the implementation of learning activities that were not yet based on Deep Learning Lesson Planning (RPM), the use of predominantly conventional teaching methods, and the limited utilization of learning media. This study aimed to describe the improvement of students’ learning outcomes on the characteristics of plane figures through the Cooperative Learning Make a Match model assisted by Wordwall in Grade IV of SDN 20 Binuang Kampung Dalam, Padang City. This research employed Classroom Action Research (CAR) using qualitative and quantitative approaches conducted in two cycles. Each cycle consisted of planning, implementation, observation, and reflection stages. The subjects were one teacher and 24 fourth-grade students in the January–June semester of the 2025/2026 academic year. Data were collected through RPM observation, teacher and student activity observations, and assessments of affective, psychomotor, and cognitive learning outcomes. The results showed continuous improvement in each cycle. The RPM score increased from 89.58% to 95.83%. The implementation of learning activities by both the teacher and students improved from 88.75% to 97.50%. Students’ learning outcomes also increased, with affective scores rising from 76.56 to 91.32, psychomotor scores from 76.30 to 92.19, and cognitive scores from 78.54 to 91.25. Therefore, the Cooperative Learning Make a Match model assisted by Wordwall effectively improved students’ learning outcomes on the characteristics of plane figures.